To evaluate the efficacy of nebulized budesonide compared to oral prednisolone in the management of moderate exacerbation of acute asthma - Sharma, Sushil; Harish, Rekha; Dutt, Neeti; Digra, Kishour Kumar (International Journal of Contemporary Pediatrics, 2017)
Background: Corticosteroids are extremely effective drugs and are used extensively in the management of asthma. Inhaled corticosteroids may offer some benefit in patients with mild to moderate obstruction in acute exacerbation and also offer the advantage of administration directly to the lungs. Hence this study was done to evaluate the efficacy of nebulized budesonide as compared to oral prednisolone in the management of moderate exacerbation of acute asthma. Methods: A total of 80 children attending pediatric emergency of SMGS Hospital Jammu aged 1 to 18 years with a moderate exacerbation of asthma despite three salbutamol nebulizations were enrolled and randomized into two groups. First group recieved nebulized budesonide (800 mcg) at hourly intervals for three doses followed by twice a day (n=37) while second group recieved oral prednisolone 2 mg/kg/day in two divided doses (n=43). Both groups continued to receive oxygen inhalation and nebulized salbutamol (0.15 mg/kg/dose) initially at hourly intervals for 3 doses followed by 6 hourly. The pattern of response as observed by the pulmonary scores in the two groups was compared. Results: The pulmonary scores were significantly improved at 1, 2 and 6 hours after starting treatment in the budesonide group as compared to prednisolone group (p < 0.01) although the difference was not significant after 12 hours. Oxygen saturation also showed a significant early improvement. Conclusions: This early demonstrable significant improvement in the clinical parameters of the inhaled budesonide group apparently suggests that inhaled budesonide may be efficacious in treating moderate exacerbations of asthma.